2006
DOI: 10.1016/j.jimonfin.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The (partial) rehabilitation of interest rate parity in the floating rate era: Longer horizons, alternative expectations, and emerging markets

Abstract: This paper examines several new empirical findings in the study of uncovered interest parity. It reviews recent developments in the study of long-horizon interest parity regressions, the implications of relaxing the rational expectations methodology and the characteristics of results pertaining to the non-G7 currencies, including those in less developed economies. In brief, the evidence against uncovered interest parity in the current floating rate era is not as great as is commonly thought, although it is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(154 citation statements)
references
References 43 publications
5
144
3
2
Order By: Relevance
“…This same pattern holds in Uganda as well. This finding is consistent with the results in Chinn (2006).…”
Section: Wwwccsenetorg/ijefsupporting
confidence: 94%
See 3 more Smart Citations
“…This same pattern holds in Uganda as well. This finding is consistent with the results in Chinn (2006).…”
Section: Wwwccsenetorg/ijefsupporting
confidence: 94%
“…In fact, UIP holds better in Bolivia than even Poghosyan et al (2008) have found for Armenia. He also finds that, unlike Chinn (2006), the bias increases as the maturity horizon increases. In particular, the estimated beta ranges from about 0.31 at the one-month horizon to 0.21 at the three-month horizon and 0.10 at the 12-month horizon.…”
Section: Review Of the Empirical Literaturementioning
confidence: 94%
See 2 more Smart Citations
“…Alternatively, interest differentials do not predict either well, or the direction, of subsequent exchange rate changes implied by interest rate parity. Chinn (2006) highlight these well known facts. One way to explain the failure of uncovered interest parity combined with rational expectations (sometimes called the unbiasedness hypothesis)…”
Section: The Risk Premium and Order Flowmentioning
confidence: 76%